Mechanically Robust Transparent Anti‐Icing Coatings: Roles of Dispersion Status of Titanate Nanotubes. Issue 18 (30th July 2018) - Wu, Xinghua; Tang, Yuxin; Silberschmidt, Vadim V.; Wilson, Peter; Chen, Zhong
Abstract: Ice accretion on automobiles, aerospace components, precision instruments, and photovoltaic devices detrimentally affect their performance and increase the maintenance cost. Despite significant efforts devoted to the investigation of anti‐icing coatings in the past decades, mechanically robust and transparent anti‐icing coatings are rarely reported. In this study, titanate nanotubes are used as filler to prepare mechanically robust anti‐icing coatings with a sol‐gel method. Specially, the effect of dispersion status of nanotubes on the transmittance, surface roughness, and water repellency is investigated. The optimized smooth, transparent coating exhibits higher water repellency and better anti‐icing performance in terms of ice‐adhesion strength, icing delay time, and ice‐nucleation temperature than the rough one. Much higher hardness and scratch resistance than that of commercially available icephobic or anti‐icing coatings is obtained on the smooth, transparent sample; the coating also presents good adhesion to the substrate. Abstract : Dispersion status of elongated titanate nanotubes in sols is investigated. By applying mechanical force for different duration, coatings with different transmittance and water repellency are obtained. Comparison of coatings with distinct dispersion status of nanotubes verifies that coatings with uniform dispersion of nanotubes exhibit better anti‐icing performance than those with aggregated ones.